2017
DOI: 10.1021/acs.energyfuels.7b00626
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Bulk Kerogen Porosity: Methods for Control and Characterization

Abstract: 9Shale gas is an unconventional source of energy, which has attracted a lot of attention during the 10 last years. Kerogen is a prime constituent of shale formations and plays a crucial role in shale gas 11 technology. Significant experimental effort in the study of shales and kerogen has produced a 12 broad diversity of experimentally determined structural and thermodynamic properties even for 13 samples of the same well. Moreover, proposed methods reported in the literature for constructing 14 realistic bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 76 publications
4
82
0
Order By: Relevance
“…The difference between the PV1-TOC and PV2-TOC covariance (Figure 12a) was consistent with those described by Wang et al [66]. Some researchers have found that mesopores consisted of elliptical organic matter pores as well, as there were quite a few inorganic matter pores with various morphologies based on FE-SEM [71][72][73][74]. It is well documented that considerable micropores are formed within the macromolecular structure of organic matter [75].…”
Section: Pore Structure Parameters and Their Controlling Factorssupporting
confidence: 88%
See 2 more Smart Citations
“…The difference between the PV1-TOC and PV2-TOC covariance (Figure 12a) was consistent with those described by Wang et al [66]. Some researchers have found that mesopores consisted of elliptical organic matter pores as well, as there were quite a few inorganic matter pores with various morphologies based on FE-SEM [71][72][73][74]. It is well documented that considerable micropores are formed within the macromolecular structure of organic matter [75].…”
Section: Pore Structure Parameters and Their Controlling Factorssupporting
confidence: 88%
“…Energies 2020, 13, x FOR PEER REVIEW 14 of 22 [83], so the microporous structure, related to the macromolecular structure of organic matter, may not become complicated as the organic matter content increases. The multifractal parameters for q > 0 corresponded to the dominance of a large concentration of the pore volume, and the parameters for q < 0 could be mainly affected by a small concentration of the pore volume [53,60,74]. As mentioned above, the PSDs of mesopores were unimodal.…”
Section: Multifractal Characteristics Of Micropores and Mesoporesmentioning
confidence: 74%
See 1 more Smart Citation
“…Various techniques were used to characterize pore systems of shale reservoirs, such as high pressure mercury injection, low pressure N 2 adsorption, CO 2 adsorption, and scanning electron microscopy (SEM). 10,[20][21][22] From these techniques, low pressure N 2 adsorption and SEM have been accepted as the most effective techniques for characterizing pore structures in shale. 13,21,23,24 It is widely accepted that pore volume and surface area are mainly affected by nanoscale pores, and most of these nanoscale pores lie in the range of low pressure N 2 adsorption scale.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoscale organic pores, which contribute to the largest part of the total pore volume, are the main storage space for shale gas (Wang Min et al, 2016). Meanwhile, it is well documented that some nanoscale organic pores (<2 nm) are formed within the three-dimensional (3D) molecular structure, and their pore structure parameters are controlled by the molecular composition and spatial structure of the organic matter (Bousige et al, 2016;Huang et al, 2017;Vasileiadis et al, 2017;Liu et al, 2018a). Therefore, the evaluation of gas storage and transport is strengthened by a robust understanding of the molecular structure of the organic matter.…”
mentioning
confidence: 99%